Starting from scratch: The primary hyperacidity theory of the cause of pyloric stenosis of infancy - Ian Munro Rogers (EL-Med-Pub, 2022)
The early observations of those who first described babies with pyloric stenosis (PS) are used as a backdrop for the development of the Inherited Primary Hyperacidity theory of cause. Those early truths, uncomplicated by modern technology, have acted as a springboard for pathogenesis. Hyperacidity, male predominance, family history, self-cure, enhanced appetite, and time-sensitive presentation were all well known to the early pioneers. Any system of pathogenesis must explain all these clinical features. The Inherited Primary Hyperacidity theory does this and is a credible explanation for all the clinical features established by these early pioneers. The evidence which supports a delay in maturation of the negative feedback between gastrin and gastric acidity is presented. Such a phenomenon further supports the Primary Hyperacidity theory.